Answer to: Find the inverse equation of f(x)=(x-6)^2 -1. By signing up, you'll get thousands of step-by-step solutions to your homework questions...
The steps for finding the inverse of a function, where they've given you a formula for the function, are these:Replace "f(x)" with y. Try to solve the equation for x=. Swap the x's and the y. Replace y with "f−1(x)"...
Find the inverse of the function f(x)=−4+ln x. Inverses, Logarithmic vs. Exponential: Given a function e.g. f(x) that takes the variable x as an input and produces y as an output, the inverse of that function would be a function e.g. g(y) that takes y as an input ...
英文数学题.Find the inverse of each of the following functions.1.f:x=x/x-2,x∈R and x≠22.f:x=2x+1/x-4.x∈R and x≠4
Find the inverse ofy=9x. Finding Inverse of a Function: To find the inverse of a functiony=f(x): (i) Interchange the variablesxandy. (ii) Solve the resultant equation foryand this would give the inverse function which is denoted byf−1(x). ...
2.Find a formula for the inverse of the function.y = 9x的3次方 + 8y=?3.Solve each equation for x. (Enter an exact answer.)(a) ln(ln(x)) = 1x=()?(b) e的ax次方 = Ce的bx次方, where a 不等于 bx = ()? 相关知识点: ...
Step 2:Determine the domain of the function,f(x). Step 3:Replacef(x)withy, and then swap the variablesxandy. Solve the resulting equation fory. Step 4: f −1 ( x ) y f(x) How to Find the Inverse of a Rational Function Vocabulary and Formulas ...
Seect the correct answer and then click Done.Find the inverse of the relation y= 2x +3, and then choose the correct statemen from the list below.ⓐ Both the equation and it inverse are functions.⑥ Only the equation is a function.Only the inverse is a function. Neither the equation ...
determine the equation for the inverse function of y=(x+3)^3+9 Answers · 1 Use the definition of inverses Answers · 1 inverse derivative: y=sec^-1 1/t Answers · 1 Find the inverse function of f(x)=x^3+5 Answers · 2 How to tell if a function is inverse Answers ·...
Find the Inverse f(x) = log of x Writef(x)=log(x)f(x)=log(x)as anequation. y=log(x)y=log(x) Interchange thevariables. x=log(y)x=log(y) Solve foryy. Tap for more steps... Rewrite theaslog(y)=x. log(y)=x Rewritelog(y)=xin exponential form using the definition of a...